Influence of lactic-acid bacteria feed supplementation on free amino acid levels in serum and feces of rainbow trout (Oncorhynchus mykiss, Walbaum 1792) - Carneiro, Gabriel R. A.; Opazo, Constanza; Do Santos, Gustavo Ramalho Cardoso; Pereira, Henrique Marcelo Gualberto; Monnerat, Gustavo; Opazo, Rafael (Frontiers in Marine Science, 2023)
Lactic-acid bacteria in particular have adequate probiotic capacities and have been widely studied for their contributions as intestinal microbiota. The study involved supplementing the feed of rainbow trout (O. mykiss) weighing 73.9±10 g with mono-strains of P. acidilactici or L. lactis at a dosage of 5 x 10 8 CFU per gram of feed for 60 days. This included a Control group that did not receive probiotics supplementation. The study evaluated growth and feed conversion indices, free amino acid levels in serum and feces, as well as the relative gene expression of four genes encoding amino acid solute carrier transporters (SLC).The trout rearing conditions corresponded to 100-liter tanks with independent closed recirculation systems for each tank. The water replacement rate was set at 80% of the total volume daily, with the temperature controlled at 15 ± 0.3 °C. The proximate composition of the basal commercial diet used in the study was as follows: crude protein 2 49.8%, fat 32.1%, fiber 1.31%, ash 13%, and moisture 8.3% on a dry matter basis. This diet was offered at a feeding rate of 2% of body weight per day. No significant differences (p > 0.05) in between the experimental groups. However, significant differences in the free amino acid levels in feces and serum samples (p ≤ 0.05) did occur. In the feces samples, glutamate, lysine, proline, and tyrosine, and in the serum samples, arginine, iso/leucine, phenylalanine, proline, serine, threonine, and valine, showed significantly higher levels in the P. acidilactici group compared to the Control group. In addition, significant downregulation (p ≤ 0.05) of the slc6a19 and slc7a9 genes was observed in the supplemented probiotic groups; genes encoding transporters with broad specificity, including neutral and cationic amino acids. P. acidilactici, an autochthonous rainbow trout strain, ultimately showed better effects on amino acid levels in feces and serum than the non-autochthonous L. lactis strain. However, the increase in amino acid levels, mainly in the serum, resulting from P. acidilactici supplementation, did not lead to improved trout growth or feed conversion.